2021
DOI: 10.1007/s11096-021-01241-2
|View full text |Cite
|
Sign up to set email alerts
|

Reducing corticosteroid phobia in pharmacy staff and parents of children with atopic dermatitis

Abstract: Background Besides physicians, pharmacy staff has an important role to inform patients on appropriate medication use. However, they might also experience corticophobia themselves, affecting patient counseling and subsequently patient’s disease management. Objective Implementation of an intervention for pharmacy staff to improve knowledge and stimulate positive perceptions towards TCS use, in order to reduce corticophobia in pharmacy staff and parents of young AD patients. Setting Nine community pharmacies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 32 publications
(46 reference statements)
0
28
0
Order By: Relevance
“…After education, we found approximately 20% decrease in corticophobia, leading beliefs to be comparable to dermatologists, which can be seen as the gold standard 9 . The size of this improvement is similar to a personalized face‐to‐face intervention targeted at pharmacists, adding support to the case for digital education as an efficient tool 28 . Furthermore, almost all responders felt more competent with treatment of AD after digital interactive education.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…After education, we found approximately 20% decrease in corticophobia, leading beliefs to be comparable to dermatologists, which can be seen as the gold standard 9 . The size of this improvement is similar to a personalized face‐to‐face intervention targeted at pharmacists, adding support to the case for digital education as an efficient tool 28 . Furthermore, almost all responders felt more competent with treatment of AD after digital interactive education.…”
Section: Discussionmentioning
confidence: 54%
“… 9 The size of this improvement is similar to a personalized face‐to‐face intervention targeted at pharmacists, adding support to the case for digital education as an efficient tool. 28 Furthermore, almost all responders felt more competent with treatment of AD after digital interactive education. Finally, we report lasting effects of digital education on knowledge of TCS, practices, and corticophobia of HCPs.…”
Section: Discussionmentioning
confidence: 96%
“…More specifically, several studies have identified the community pharmacist as one of the main references for the patient affected by dermatitis (Wong et al 2017;Smith et al 2020). If properly educated on the phenomenon, we believe that pharmacists could be instrumental in helping the patients overcome corticophobia (Koster et al 2021), supporting the adherence to TCT and ultimately mediating a positive prognosis of the dermatological disorder . A higher patient satisfaction with information on TCT was indeed predictive of more positive opinions about the use of corticosteroids, resulting in improved adherence .…”
Section: Section B: Treatment and Role Of The Pharmacistmentioning
confidence: 85%
“…In addition to a proper information on the treatment, many factors can influence the compliance to this therapy: corticophobia should be considered as a relevant one (Aubert-Wastiaux et al 2011). In support of this vision, a recent work described that the education of pharmacy staff and targeted patient counseling by intercepting those at higher risk, was effective in reducing corticophobia (Koster et al 2021).…”
Section: Section B: Treatment and Role Of The Pharmacistmentioning
confidence: 99%
“…However, video-assisted elucidation, written pamphlets, practical demonstrations by nurses, and establishing doctor–patient trust can alleviate steroid phobia. 27…”
Section: Pharmacologic Treatmentsmentioning
confidence: 99%